Reduction of 4-nitrophenol Mediated by Silver Nanoparticles Synthesized using Aqueous Leaf Extract of Peronema canescens - Salprima Yudha S; Aswin Falahudin; Risky Hadi Wibowo; John Hendri; Dennie Oktrin Wicaksono (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
In this study, we developed an alternative of 4-nitrophenol reduction mediated by silver nanoparticles (AgNPs) which was synthesized using aqueous extract of the Peronema canescens leaf through an eco-friendly approach. The reducing 4-nitrophenol to 4-aminophenol mediated by AgNPS in the presence of sodium borohydride as a hydrogen source proceeded rapidly at room temperature without any additional treatments. The AgNPS synthesis was simple and was carried out under mild conditions. Ultraviolet–visible spectroscopy was performed to examine the properties of the obtained AgNPs, which displayed an absorption peak at 431 nm. A transmission electron microscopy analysis revealed that the AgNPs were spherical in shape and had an average particle size of 19 nm as determined by particle size analysis. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).